Лесные домишки: [рассказы и сказки] / Виталий Бианки - Бианки Виталий Валентинович (Внеклассное чтение, 2011)
Экземпляры: М/а ДБ (20131119) / Инвентарный номер: 100331 / Цена: 66.50 / Авт.знак: Б 59 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6